Beyond fossil fuels: Charting a sustainable transport pathway for Bangladesh at COP30 - Raihan, Selim; Khan, Fariha; Pal, Barun Deb (SANEM Publications, 2025)
The transport sector of Bangladesh, while on one hand is an important driver of economic growth, is also one of the major contributors to Greenhouse Gas (GHG) emissions. This policy brief outlines the current challenges, reviews government actions, proposes alternative solutions, and assesses their potential economic impacts in the context of Bangladesh’s preparation for the 30th COP and the development of the third Nationally Determined Contribution (NDC). The analysis highlights ongoing efforts to align climate resilience with the national policies of the transport sector. However, key challenges remain, including continued reliance on fossil fuels, high costs associated with Electric Vehicle adoption, and infrastructural barriers. To address these issues, we recommend enhanced policy coordination across sectors, expansion of financial incentives for transitioning to greener transport options, embedding climate risk assessments into ongoing and future transport infrastructures, and investment in research on the feasibility and challenges of overall green energy transition in the transport sector.